2014
DOI: 10.1016/j.nano.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle targeting to diseased vasculature for imaging and therapy

Abstract: Significant challenges remain in targeting drugs to diseased vasculature; most important being rapid blood flow with high shear, limited availability of stable targets, and heterogeneity and recycling of cellular markers. We developed nanoparticles (NPs) to target degraded elastic lamina, a consistent pathological feature in vascular diseases. In-vitro organ and cell culture experiments demonstrated that these NPs were not taken up by cells, but instead retained within the extracellular space; NP binding was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…However, a recent study argue against the involvement of SPARC in nab-paclitaxel treatment of metastatic breast cancer [280]. More recent examples are biodegradable albumin-based nanoparticles containing contrast agents for magnetic resonance imaging of hepatocellular carcinoma [281], iron-oxide containing magnetic nanoparticles for tumor imaging [227], anti-elastin antibody and EDTA-loaded nanoparticles for targeting to degraded elastic lamina of vascular diseases [228,229] as well as inhalable nanoparticles containing drugs targeting lung cancer [230]. Examples of therapeutic molecules that have been encapsulated in albumin-based nanoparticles are listed in Table 2.…”
Section: Albumin-based Nanoparticlesmentioning
confidence: 99%
“…However, a recent study argue against the involvement of SPARC in nab-paclitaxel treatment of metastatic breast cancer [280]. More recent examples are biodegradable albumin-based nanoparticles containing contrast agents for magnetic resonance imaging of hepatocellular carcinoma [281], iron-oxide containing magnetic nanoparticles for tumor imaging [227], anti-elastin antibody and EDTA-loaded nanoparticles for targeting to degraded elastic lamina of vascular diseases [228,229] as well as inhalable nanoparticles containing drugs targeting lung cancer [230]. Examples of therapeutic molecules that have been encapsulated in albumin-based nanoparticles are listed in Table 2.…”
Section: Albumin-based Nanoparticlesmentioning
confidence: 99%
“…Our previous studies with polymeric NPs have shown that ~150–200 nm size particles enter through endothelium and bind to elastic lamina in the medial layers [15]. Thus all NPs intended for use in further studies were prepared by 45 minutes of probe sonication to obtain particles of ~150 nm size.…”
Section: Resultsmentioning
confidence: 99%
“…These previous studies led us to develop a nanoparticle-based targeted chelating-agent delivery that could lower the dosage required and improve the bioavailability of the chelating agent [14]. We recently showed that elastin antibody-coated nanoparticles can be targeted to vascular calcification sites [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies primarily targeted vascular cells, although targeting of ECM molecules or blood clots might avoid the potential challenges associated with cell-internalization mechanisms and processes of drugs [18]. To this end, only a few studies target ECM itself, with none aiming at drug delivery to the CNS [19,20]. Therefore, we wanted to test if it is possible to target CNS lesions that are associated with diseased blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The higher accumulation of the fibrin NP is probably due to the fact that they could only be incorporated into forming blood clots, which usually happens only at damaged tissue, whereas nidogen is more widely expressed which can lead to off-target accumulation. In comparison, Sinha et al developed poly (d,l-lactide) nanoparticles functionalized with antibodies to target vascular degraded-elastic fibers [20]. They demonstrated enhanced binding in different animal models of vascular disease, but did not investigate CNS blood vessels.…”
Section: Discussionmentioning
confidence: 99%